The Relationship between Air Pollution, Economic Growth, and Life Expectancy: Empirical Evidence from Indonesia - Abdul Bashir; Liliana Liliana; Ariodillah Hidayat; Suhel Suhel (Signifikan: Jurnal Ilmu Ekonomi, 2022)
This study investigates the relationship between air pollution, economic growth, and life expectancy in Indonesia. The observation period during 1985-2019 used time-series data obtained from the World Bank. Quantitative approach by applying two main models, namely the autoregressive distributed lag (ARDL) model by considering the effect of time-lapse and Granger causality with vector error correction method. Research findings prove that air pollution has a negative and significant effect on life expectancy in the long run. Economic growth has a positive and significant effect on life expectancy. In the short run, the current life expectancy is positively and significantly influenced by the life expectancy of the previous period. Air pollution has a negative and significant effect on life expectancy, and economic growth has a negative and significant effect on life expectancy. Another finding in the Granger causality model is a two-way relationship between air pollution and life expectancy. Other evidence exists of a two-way relationship between economic growth and air pollution. In addition, evidence of a unidirectional relationship of economic growth with life expectancy in the short run. The cointegration equation shows evidence of a long-run relationship between air pollution, economic growth, and life expectancy..How to Cite:Bashir, A., Liliana, L., Hidayat, A., Suhel, S., Hamidi, I., & Atiyatna, D. P. (2022). The Relationship between Air Pollution, Economic Growth, and Life Expectancy: Empirical Evidence from Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 11(1), 125-144. https://doi.org/10.15408/sjie.v11i1.23334.